Synthesis and Preliminary Properties of Novel Poly(aryl ether)s Containing β-Naphthalene Pendant Group. (27th August 2014) - Wang, L.; Tao, D.; Xiang, X. Z.; Zhu, G. M.
Abstract : Two novel poly(aryl ether)s containing β -naphthalene pendant group were synthesized and the structures of these polymers were confirmed by 1 HNMR spectroscopy. The polymers exhibited good thermal stabilities with high Tg of 256°C and 274°C, respectively. The polymers are soluble in common organic solvents, such as DMAc, DMSO, CH2 Cl2, and CHCl3, and can be electrospun into microfiber (1–5  µ m) with lots of nanopores (<100 nm) from CHCl3 solution. These fibers showed high hydrophobicity, and the contact angle of fibers is above 120°.